Anxiety about English Public Speaking in the Students of English Education Department - Dwi Ajeng Tristanti; Wariyati (Medan Resource Center, 2023)
Speaking in spoken English is the act of conveying information or expressing thoughts and feelings. This study described how to analyze students' speaking fear in English Public Speaking at eighth semester Muslim Nusantara University Al-Washliyah Medan English Education Department. The qualitative research method was applied in this study. The researcher employed observation, interview, and questionnaire to gather the data. Three main stages of data analysis were used by the researcher: data reduction, data display, and conclusion drawing verification. Following a study of the data, the researcher came to the following conclusions about speaking fear among students at eighth semester Muslim Nusantara Al-Washliyah Medan English Education Department: First, the researcher discovered that the following factors contributed to students' speaking anxiety in English Public Speaking: self-prediction of fear, illogical faith, oversensitivity to threat, anxiety sensitivity, incorrect attribution of body signal, and low self-efficacy. Second, students' lack of speaking confidence in English, fear of making mistakes when speaking, nervousness when the teacher asks them to speak up, and shyness to perform in front of the class are the causes of students' speaking anxiety.